Knowledge regarding Child Development among Mothers attending Clinic of Bheri Hospital, Banke - Chand, Ambika; Ranjitkar, Uma Devi (Journal of Nursing Education of Nepal, 2023)
Introduction: Mothers should have knowledge that every child is unique in his/ her abilities. Mothers having more knowledge about child’s uniqueness and their developmental progress, prove to be more efficient mothers. A mother who has the proper knowledge of a child’s development can be more alert for early screening of the child for any development. The objective of the study was to find out the knowledge of mothers regarding the development of their children. Methods: A descriptive cross-sectional study was conducted in MCH clinic of Bheri Hospital Nepalgunj. Conveniently selected 66 mothers with at least one child aged under three years of age were included in the study. In person interviews were conducted using a semi structured interview questionnaire. The ethical approval was obtained from Institutional Review Committee of Institute of Medicine. Data analysis was done with the use of descriptive and inferential statistics. Results: Finding showed that only 21.2% respondents had good knowledge, 18.2% had average knowledge and 60.61% had poor knowledge regarding child development. Conclusion: Mothers attending MCH clinic tend to have poor knowledge regarding child development. Therefore, Informational programs should be launched for mothers to upgrade their knowledge about child development and able them to take prompt action for any developmental deviation of their children. DOI: https://doi.org/10.62143/2cy4fy15